Functional characterization of a novel aminoglycoside phosphotransferase, APH(9)-Ic, and its variant from Stenotrophomonas maltophilia - Shi, Weina; Lu, Junwan; Feng, Chunlin; Gao, Mengdi; Li, Anqi; Liu, Shuang; Zhang, Lei; Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Lin, Xi; Li, Kewei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background The intrinsic resistance mechanism plays an essential role in the bacterial resistance to a variety of the antimicrobials. The aim of this study is to find the chromosome-encoded novel antimicrobial resistance gene in the clinical isolate. Methods The function of the predicted resistance gene was verified by gene cloning and antibiotic susceptibility test. Recombinant protein expression and enzyme kinetic studies were performed to explore the in vivo activity of the enzyme. Expression of the resistance gene exposed to antimicrobial was determined by RT-qPCR. Whole genome sequencing and bioinformatic analysis were applied to analyze the genetic context of the resistance gene. Results The novel aminoglycoside (AG) resistance genes designated aph(9)-Ic and aph(9)-Ic1 confer resistance to spectinomycin, and a recombinant strain harboring aph(9)-Ic (pMD19-T-aph(9)-Ic/DH5α) showed a significantly increased minimum inhibitory concentration (MIC) level against spectinomycin compared with the control strains (DH5α and pMD19-T/DH5α). The result of the kinetic analysis of APH(9)-Ic was consistent with the MIC result for the recombinant pMD19-T-aph(9)-Ic/DH5α, showing the efficient catalytic activity for spectinomycin [kcat/Km ratio = (5.58 ± 0.31) × 104 M−1·s−1]. Whole-genome sequencing demonstrated that the aph(9)-Ic gene was located on the chromosome with a relatively conserved genetic environment, and no mobile genetic element was found in its surrounding region. Among all the function-characterized resistance genes, APH(9)-Ic shares the highest amino acid sequence identity of 33.75% with APH(9)-Ia. Conclusion We characterized a novel AG resistance gene aph(9)-Ic and its variant aph(9)-Ic1 that mediated spectinomycin resistance from S. maltophilia. The identification of the novel AG resistance genes will assist us in elucidating the complexity of resistance mechanisms in microbial populations.